Odor-Induced Vomiting Is Combinatorially Triggered by Palp Olfactory Receptor Neurons That Project to the Lobus Glomerulatus in Locust Brain - Sun, Liyuan; Pan, Xueqin; Li, Hongwei; Zhang, Xinyang; Zhao, Xincheng; Zhang, Liwei; Zhang, Long (Frontiers in Physiology, 2022)
Although vomiting is commonly recognized as a protective approach in response to toxic stimuli, the elaborate sensory processes and necessary molecular components are not fully clear, which is due to a lack of appropriate experimental animal models. Locust vomits to volatile chemicals, providing one candidate vomiting model. Here, we identified a panel of chemical cues that evoked evident vomiting in locust nymphs and demonstrated the selected combinatorial coding strategy that palp, but not antennae olfactory receptor neurons (ORNs) employed. Specifically, knocking down individual palp odorant receptors (ORs) OR17, OR21 and OR22 attenuated the vomiting intensity evoked by E-2-Hexenal and Hexanal, while suppression of OR12 and OR22 augmented vomiting to E-2-Hexenal and 2-Hexanone respectively. Furthermore, dual-RNAi treatment against OR17 or OR21 together with OR22 resulted in a much lower response intensity than individual OR suppression. Furthermore, OR12 was revealed in palp sensilla basiconica (pb) subtype 3 to tune the neuronal decaying activity to E-2-Hexenal. Finally, anterograde labeling of individual pbs indicated that palp ORNs primarily projected into the lobus glomerulatus and further relayed into posterior lobe of the calyx. Together, the establishment of an olfaction-inducible vomiting model in locusts deepens understanding of olfactory coding logics and opportunities to understand the neural basis underlying animal vomiting.